Improving prenatal detection of congenital hand defects through collaborative goal-directed antenatal care: a case report on symbrachydactyly - Nnabuike Chibuoke Ngene; Lawrence Chauke (Elsevier, 2020)
Background: Prenatal ultrasonography for the detection of fetal structural anomaly is an important component of antenatal care. During the assessment, proximal limb deformities are readily diagnosed. Distal limb, especially digit, abnormalities, however, may be difficult to detect, particularly if the ultrasonography is performed in the third trimester, and the deformity is unilateral and isolated. Case: A 24-year-old primigravida booked for antenatal care with a general practitioner had threatened miscarriage at 12 weeks of gestation, and at 34 weeks was referred to an obstetrician for further care and delivery. The growth ultrasonographic examination was normal but at 40 weeks of gestation she developed antepartum haemorrhage of unknown origin. She had a caesarean delivery and a female baby with "rudimentary" left fingers ("isolated symbrachydactyly") was delivered. The parents were counselled and they declined further assessment of the baby by a hand surgeon and a clinical geneticist. At 3 years of age, the baby had normal development and "is using her hand even without fingers," according to the mother. Conclusion: Collaborative goal-directed antenatal care that involves different categories of healthcare professionals, but particularly a certified sonologist who performs fetal anomaly ultrasonography, is essential for the detection of congenital hand defects. Adequate counselling is essential for the satisfaction of the baby's family.